Strategi Komunikasi Pemerintah Kabupaten Tapanuli Selatan melalui Media Sosial dalam Mensosialisasikan Program 1000 Kolam - Fazri Fadhilah Tambunan; Indira Fatra Deni Peranginangin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to explore the communication strategies of the South Tapanuli Regency Government through social media in promoting the 1,000 Ponds Program, a community-based fish self-sufficiency initiative that is a priority for regional food security development. The study examines the processes, meanings, and challenges of local government communication amid the digital divide, which remains a problem in rural areas. The study employs a qualitative approach with a case study design based on an interpretive paradigm. Data were collected through semi-structured interviews, non-participatory observation, and a document review of officials and staff at the South Tapanuli Regency Communication and Information Technology Office, as well as community leaders selected using purposive and snowball sampling techniques. Data analysis was conducted using the Miles and Huberman interactive model. The research results reveal five main findings: collaborative cross-agency communication strategy planning; the selection of social media platforms based on audience segmentation and analytical data; planned content production that is constrained by limited human resources; public interaction that remains dominated by one-way communication, although it is beginning to evolve toward a dialogic approach; and the implementation of a hybrid communication strategy in response to the digital divide caused by geographical conditions. These findings enrich New Media Theory and the Theory of Government Digitalization by demonstrating that the digitalization of local government communication is a contextual process. The study recommends strengthening digital human resource capacity, streamlining content approval mechanisms, integrating digital and non-digital communication strategies, and conducting further research that incorporates the perspectives of program beneficiaries.